Analisis Persepsi Harga Terhadap Keputusan Pembelian Sepeda Listrik di Kota Serang - Dian Novita; Sabinah; Syamsul Hidayat (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine the perception of price and product quality on the Purchase Decision of Electric Bikes in Serang City. This research was conducted by sampling using survey method. This study took a sample of 104 respondents and the hypothesis was tested with the help of the SPSS program version 26. From the results of the analysis obtained that price has a positive influence on consumer loyalty.